Third Way, New Labour, and the Challenges to Economic and Monetary Union Macropolicies - Arestis, Philip; Sawyer, Malcolm (Wirtschaft und Gesellschaft, 2002)
We have sketched in this paper the theoretical foundations of the 'third way', and suggested that they are rooted in the New Keynesian tradition. Furthermore, we argued that the EMU theoretical foundations are embedded in this theoretical approach. We have examined the policy implications of the EMU, along with its theoretical and institutional dimensions surrounding monetary and fiscal policies. The real challenges to EMU macropolicies lie in their ability to move the euro area to a full employment situation with low inflation. They are actually unsatisfactory to withstand the challenge. We have proposed a number of changes that would include the following elements. First, a revamped EIB to supplement the ECB is vitally necessary. Second, any political constraints on national budget positions should be removed, and national governments set fiscal policy as they deem appropriate. Third, institutional arrangements for the co-ordination of national fiscal policies be strengthened. Fourth, EU institutional arrangements are required for the operation of an EU fiscal policy, and to ensure that monetary authorities do not dominate economic policy making. Fifth, serious co-ordination of monetary and fiscal policies is paramount.